Exploring the dynamics of human resources apology in organizational communication - A. Rajabipoor Meybodi; M. Sabokro; A. Solhjoo; E. Hosseini; F. Forghani Elahabadi (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: The emotional expression of feelings and the satisfaction of social needs are two primary purposes of many communication interactions in an organization. As a universal aspect of human interaction, the apology has sparked great interest in its study across a wide range of disciplines. However, the human resources apology has not been involved integrally in the context of organizational communication. Therefore, the research question is, what are the dynamics of human resources apology in organizational communication in Iran?METHODS: This was a qualitative study conducted using grounded theory. The research was conducted, and sampling was theoretical in municipalities in Iran. For data collection, semi-structured in-depth interviews with the 5W1H technique were conducted with 13 managers, who respond to citizens’ requests in the central building of municipalities in Iranian provinces. The researched community comprises human resource managers with at least five years of beneficial work experience in the municipality and relevant knowledge of apology. Targeted sampling has been done based on the researcher’s considerations.                                                         FINDINGS: The analysis of the interviews resulted in a set of fundamental topics collected during the open coding process. Sixteen categories were extracted from these fundamental topics. Then, in the axial coding stage, the link between these categories was determined under the following headings causal conditions, core category, contextual conditions, intervening conditions, strategies, and consequences of human resources apology in the form of an axial coding paradigm. In the present study, data analysis was performed using ATLAS. ti software version 8 in three stages of primary, central, and selective coding, which resulted in the identification of 5 categories, 15 central concepts, and 126 final codes.CONCLUSION: The developed process model provides a comprehensive understanding of the human resources apology process in municipalities in Iran. The study highlights the importance of conflict management, individual behavior, motivation, audience strength, acceptability, apology graph, apology method, audience identity, communication quality, patience, and incompatibility in the human resources apology process.